ANALISIS FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ABORTUS PADA KARYAWATI - Yekti Satriyandari (Junal Kebidanan Dan Keperawatan Aisyiyah, 2017)
Abstract: This research aims to see a model of the provision of breastfeeding exclusively on an employee in Institute of Health Science ‘aisyiyah. A method of research is qualitative approach (in-depth interview) that stress to non numerical analysis and analysis on the interpretative social phenomena ..The validity of the data with the technique of triangulation .Processing and analysis of data using a method of colaizzi .The results of research shows a model of granting exclusive breastfeeding employee stikes aisyiyah in by squeezing breastfeeding and the provision of breastfeeding when abandoned by working with using a spoon or teat. The benefits of granting exclusive breastfeeding is the baby immune. Suggested that Stikes Aisyiyah can improve facilities and infrastructure and providing a special room breastfeeding corner. Keyword: abortus, causing abortion, jobs